2005
DOI: 10.1111/j.1540-8159.2005.40011.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Congenital Junctional Ectopic Tachycardia: Prenatal Diagnosis and Successful Radiofrequency Catheter Ablation in Infancy

Abstract: It is difficult to make a definitive diagnosis of congenital junctional ectopic tachycardia (JET) in utero. We report a case in which congenial JET was suspected by fetal M-mode echocardiography. Fetal M-mode tracing of the atria and ventricle clearly showed a gradual acceleration of ventricular activity at the beginning of tachycardia, the warming-up sign of ectopic tachycardia, which was followed by simultaneous contractions of atrium and ventricle. This report also describes successful emergent radiofrequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The successful ablation sites were the para-Hisian area and midseptal region of the tricuspid annulus, as reported in previous studies 3, 4, 6. There are several ways to resolve JET, such as applying energy at the HBE recording site where the tachycardia rate can be decreased by the mechanical manipulation of the ablation catheter 15 or by the application of energy at the earliest retrograde atrial activation site when ventriculoatrial conduction is present 16 .…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The successful ablation sites were the para-Hisian area and midseptal region of the tricuspid annulus, as reported in previous studies 3, 4, 6. There are several ways to resolve JET, such as applying energy at the HBE recording site where the tachycardia rate can be decreased by the mechanical manipulation of the ablation catheter 15 or by the application of energy at the earliest retrograde atrial activation site when ventriculoatrial conduction is present 16 .…”
Section: Discussionsupporting
confidence: 54%
“…There have been only 5 cases previously reported that have required CA during a patient's infancy 2, 3, 4, 6, 7. All 5 cases were successfully ablated, but the incidence of complications was high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of the tachycardia is thought to be abnormal automaticity arising from the region of the atrioventricular junction. Congenital JET presents in infancy and is associated with high morbidity and mortality (1)(2)(3)(4)(5)(6)(7). JET presenting beyond the first 6 months of life has a variable presentation.…”
mentioning
confidence: 98%
“…8 The fetal heart rate showed incessant tachycardia of 160-180 bpm with 1:1 AV relationship. However, they observed with M-mode echocardiography that the normal time delay between peak atrial and peak ventricular contraction shortened progressively with simultaneous atrial and ventricular contraction at the beginning of tachycardia.…”
Section: Discussionmentioning
confidence: 98%